INCLUSIVE EDUCATION PERSPECTIVES: MONTESSORI AND VYGOTSKY'S APPROACHES TO CREATING A SUPPORTIVE LEARNING ENVIRONMENT FOR ALL CHILDREN - Ferdinand Salomo Leuwol; Mustofa Aji Prayitno; Taryana; Yayuk Suprihartini; Gamar Al Haddar (CV. ADIBA AISHA AMIRA, 2023)
This article delves into the application of Maria Montessori's and Lev Vygotsky's thoughts within the realm of inclusive education. Employing a descriptive comparative methodology, it meticulously scrutinizes both theorists' perspectives to uncover the convergences and divergences in their views on inclusive educational practices. Drawing upon an extensive literature analysis of the original works of Montessori and Vygotsky, as well as relevant research studies, this research aims to shed light on the synergies and disparities between their pedagogical philosophies. The research findings reveal common ground in their emphasis on active learning methodologies, recognition of the significance of progression and procedural learning, and a shared commitment to prioritizing the child's individual needs within the educational framework. Nevertheless, the research underscores the distinctive features within Montessori's advocacy for fostering independence and self-exploration, juxtaposed with Vygotsky's emphasis on the pivotal role of social interaction and guided instruction. The practical implications distilled from their respective viewpoints furnish valuable insights that resonate with the design and implementation of inclusive learning strategies. By interweaving Montessori's self-directed learning ideals with Vygotsky's scaffolding concept, the article contends that an enriched and adaptive approach to inclusive education can be cultivated. This study endeavors to enrich the discourse surrounding the integration of Montessori's and Vygotsky's pedagogical tenets, fostering a comprehensive understanding of how these distinct yet complementary philosophies can be harnessed to fashion an inclusive educational environment that not only accommodates the diverse needs of all learners but also nurtures their holistic growth